Optimal control of anti-HBV treatment based on combination of Traditional Chinese Medicine and Western Medicine. (January 2015) - Su, Yongmei; Sun, Deshun
Highlights: A Hepatitis B virus model with standard incidence rate and logistic proliferation of healthy and infected cells is considered. The optimal control problem about anti-HBV infection combination therapy of Traditional Chinese Medicine and Western Medicine is studied. Two optimal strategies with or without the impact to the infection rate by treatment are verified. The simulation is given. The comparation is given between the optimal control strategy and constant control strategy, which shows the optimal control strategy is better than constant control strategy. Abstract: In this paper, a Hepatitis B virus model with standard incidence rate and logistic proliferation of healthy and infected cells is presented. Based on this model, we study an optimal control problem about anti-HBV infection combination therapy of Traditional Chinese Medicine and Western Medicine, the optimal strategies of taking medicine are given by simulation. Two optimal strategies with or without the impact to the infection rate by treatment are compared, simulation shows the impact to the reduction of infection may be omitted when mathematical model is used to study the anti-HBV therapy which is consistent with some references. What is more, optimal control strategy with other constant control strategies are also compared, and the simulation shows the optimal control strategy is better than constant control strategies.